The effect of solubilized homologous zona pellucida on the human acrosome reaction, sperm-zona binding and motion characteristics of capacitated human spermatozoa - Bastiaan, Hadley Saville (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.